2022
DOI: 10.5435/jaaos-d-22-00463
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Evidence for Infection Reduction With Vancomycin-treated Anterior Cruciate Ligament Grafts

Abstract: Septic arthritis after anterior cruciate ligament (ACL) reconstruction is a rare but devastating complication. Several risk factors and known sources of infection have been identified in the literature. There is growing interest and supportive evidence for a targeted invention aimed at graft decontamination, which has led some surgeons to adopt the use of antibiotic solution soaks and/or wraps applied to ACL grafts before graft implantation in an attempt to reduce the risk of postoperative infection. Despite t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…All species were susceptible to vancomycin which is coherent with the findings of Pérez-Prieto et al who reported that bacterial contamination from grafts could be completely eliminated by topical application of vancomycin [ 25 ]. Thus, clinical studies showed that the postoperative infection rate after ACL reconstruction could be significantly reduced to almost 0% by soaking the hamstring tendon graft in vancomycin before it was implanted into the knee joint [ 3 , 4 , 6 , 7 , 12 , 13 , 18 , 21 , 22 , 26 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All species were susceptible to vancomycin which is coherent with the findings of Pérez-Prieto et al who reported that bacterial contamination from grafts could be completely eliminated by topical application of vancomycin [ 25 ]. Thus, clinical studies showed that the postoperative infection rate after ACL reconstruction could be significantly reduced to almost 0% by soaking the hamstring tendon graft in vancomycin before it was implanted into the knee joint [ 3 , 4 , 6 , 7 , 12 , 13 , 18 , 21 , 22 , 26 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, Vertullo et al introduced a technique of presoaking the graft in vancomycin before it is implanted into the knee joint [ 33 ]. Clinical studies subsequently have shown a significant reduction of postoperative infection rate after ACLR by this technique [ 3 , 4 , 6 , 7 , 12 , 13 , 18 , 21 , 22 , 26 , 31 ]. However, at the time this technique was introduced, the exact mechanism of contamination leading to knee joint infection after ACLR was unclear and to some extend still is.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, recent studies have proven it to be a safe technique with no increase in re‐ruptures and a similar return‐to‐play time [10, 26, 42]. Moreover, it is a cost‐effective technique [32, 42]. However, it is important to remember that all other measures to reduce infection including behavior in the operating room must be implemented and cannot be neglected.…”
Section: Preventionmentioning
confidence: 99%